Engineering of efficiency limiting free carriers and an interfacial energy barrier for an enhancing piezoelectric generation - Sohn, J; Cha, S; Song, BG; Lee, S; Kim, S; Ku, J; Kim, H; Park, Y; Choi, B; Wang, Z; Kim, J; Kim, K (2013)
The energy harvesting efficiency is of tremendous importance for the realization of a high output-power nanogenerator serving as the basis for self-powered electronics. Here we report that the device performance of a sound-driven piezoelectric energy nanogenerator (SPENG) is remarkably improved by controlling both the carrier density and the interfacial energy in a semiconducting ZnO nanowire (NW), thereby achieving its intrinsic efficiency limits. A SPENG with carrier-controlled ZnO NWs exhibits excellent energy harvesting characteristics with an average power density of 0.9 mW cm -3, as well as a near 50 fold increase in both output voltage and current compared to those of a conventional ZnO NW. In addition, we demonstrate for the first time that an optimized SPENG is large enough and very suitable to drive electrophoretic ink displays based on voltage-drive systems. This fundamental progress makes it possible to fabricate high performance nanogenerators for viable industrial applications in portable/wearable personal electronics such as electronic papers and smart identity cards. © The Royal Society of Chemistry 2013.